2010
DOI: 10.1186/ar3207
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic effect of interleukin-17A in induction of Sjögren's syndrome-like disease using adenovirus-mediated gene transfer

Abstract: IntroductionSjögren's syndrome (SS) involves a chronic, progressive inflammation primarily of the salivary and lacrimal glands leading to decreased levels of saliva and tears resulting in dry mouth and dry eye diseases. Seminal findings regarding TH17 cell populations that secrete predominantly interleukin (IL)-17A have been shown to play an important role in an increasing number of autoimmune diseases, including SS. In the present study, we investigated the function of IL-17A on the development and onset of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 39 publications
5
66
1
1
Order By: Relevance
“…The results provide evidence for the role of RORgt overexpression in CD4 + T cells in the development of spontaneous sialadenitis-like SS through downregulation of CD4 + CD25 + Foxp3 + Treg cells. Experimental evidence suggests that IL-17 produced from CD4 + T cells is directly involved in the onset of SS-like disease (11,22). However, we demonstrated in the present study the development of sialadenitis in IL-17-deficient RORgt Tg mice, indicating that IL-17 is not essential for the development of sialadenitis in RORgt Tg mice.…”
Section: Discussioncontrasting
confidence: 91%
“…The results provide evidence for the role of RORgt overexpression in CD4 + T cells in the development of spontaneous sialadenitis-like SS through downregulation of CD4 + CD25 + Foxp3 + Treg cells. Experimental evidence suggests that IL-17 produced from CD4 + T cells is directly involved in the onset of SS-like disease (11,22). However, we demonstrated in the present study the development of sialadenitis in IL-17-deficient RORgt Tg mice, indicating that IL-17 is not essential for the development of sialadenitis in RORgt Tg mice.…”
Section: Discussioncontrasting
confidence: 91%
“…Adoptive transfer of Th17 cells into the inducible IL-17A KO mice could rapidly acquire a SS profile [61]. C57BL/6J mice that receive adenovirus serotype 5 (Ad5) -IL17A vector, an SS model, express high levels of IL-17A, which correlates with recruitment of inflammatory cells [62]. In patients with Sjögren's syndrome, both systematically elevated levels of IL-17 [63,64] and presence of Th17 cells [65][66][67] in inflamed tissue have been observed in multiple studies.…”
Section: Th17 and Ssmentioning
confidence: 99%
“…Although the pathogenesis of pSS is not clarified completely, it is well established that an aberrant autoimmune response with T and B lymphocyte hyperactivity and autoantibody production represents the crucial mechanism for the induction of autoimmune epithelitis and the perpetuation of inflammation. Moreover, several lines of evidence in animal models and pSS patients suggest that the proinflammatory cytokine interleukin (IL)-17 and, therefore, IL-17-producing T helper cells (Th17) play a pivotal role in the induction and perpetuation of chronic inflammation occurring in this disease [5][6][7]. We have previously demonstrated that besides CD3 1 CD4 1 T helper type 17 (Th17) cells, a small CD3 1 T cell subset lacking both CD4 and CD8 on the cell surface (double-negative, DN), is expanded in the peripheral blood (PB), infiltrates minor salivary glands (MSGs) of patients with pSS and produces IL-17 spontaneously [8].…”
Section: Introductionmentioning
confidence: 99%